TALEMPONG PACIK TRAINING AS A STRATEGY FOR LOCAL CULTURAL PRESERVATION AND THE DEVELOPMENT OF MUSICAL INTELLIGENCE AMONG STUDENTS OF SMAN 3 PADANG PANJANG - Suhadri, Fadlika; Fulzi, Nadya (Bhandar: Harvesting Community Service in Asia, 2025)
This study examines the implementation of Talempong Pacik training as an effort to preserve traditional culture while simultaneously enhancing the musical intelligence of students at SMAN 3 Padang Panjang. The focus of this paper is on training activities conducted at SMAN 3 Padang Panjang through collective and group-based practice. The results indicate that Talempong Pacik training not only strengthens students’ understanding of local cultural identity but also improves motor coordination skills, rhythmic sensitivity, group cooperation, and interest in traditional music. These findings underscore the importance of Talempong Pacik training as part of the local content curriculum and extracurricular activities at SMAN 3 Padang Panjang. The study recommends the continuity of training programs, the provision of competent instructors, and collaboration between schools and art communities as sustainable strategies for cultural preservation.